EFFECT OF ANODIZING VOLTAGE AND TO BACCOD EXRACT ADDITION TO THE STRUCTURE OF POROUS ANODIC ALUMINUM OXIDE (PAAO) LAYER - Zein Eko Mustofa, Akhmad
Porous Anodic Aluminum oxide (PAAO) is a porous oxide layer resulting from anodization. The structure of PAAO is influenced by anodization parameters, i.e., voltage and electrolyte composition. Increasing anodization voltage can affect the process of pore formation and oxide growth during anodization. The addition of additives such as ethanol, propanol, and polyethylene glycol (PEG) can increase pore regularity and affect the structure of PAAO. In this study, the authors added tobacco extract (TE) to the oxalic acid-based anodizing solution. TE has many active compounds that may affect the pore formation and oxide growth process. Morphological analysis shows a decrease in pore diameter in the addition of tobacco extracts of 0, 0.1, and 0.5 g/L, namely 43.92, 41.42, and 37.8 nm at 40 V. In anodization with a voltage of 60 V, a decrease in pore diameter was obtained with 46.47, 34.24, and 26.8 nm for the addition of tobacco extract 0, 0.1, and 0.5 g/L. Thickness of PAAO increases from 6.45 ?m to 16.87 ?m with increasing anodization voltage and tobacco extract concentration. The increase of tobacco extract concentration can lead to the decrease of the XRD peak intensity, where the sequence of the most significant decrease was observed for the peaks of (111), (220), (200), and (311); respectively. A decrease in the intensity ratio of (111) and (220) AAO peaks indicates the influence of tobacco extract on the anodization process. Further thermal analysis by Thermo-gravimetric (TG) shows an increase in mass loss from 1.47 to 5.37% with increasing tobacco extract concentration from 0 g/L to 0.5 g/L. TG results indicate the incorporation of tobacco extract in the inner pore wall.